2022
DOI: 10.3389/fneur.2021.802413
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Stent-Induced Straightening of Parent Artery vs. Stent Struts for Intracranial Bifurcation Aneurysms

Abstract: ObjectiveThis study aims to compare the hemodynamic impact of stent-mesh and stent-induced straightening of the parent artery in intracranial bifurcation aneurysms using finite element method simulation.Material and MethodsThree intracranial bifurcation aneurysms treated with different stent-assisted coil embolization were evaluated. Simulation using the finite element method was conducted for Solitaire, LVIS and Neuroform stents. Four models of each stent were established, including a pre-treatment baseline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“… 14 ) Therefore, straightening the parent artery with a stent may be the optimal way to reduce the recurrence of intracranial bifurcation aneurysms. 13 ) It has also been reported that parent artery straightening is likely to be involved in higher occlusion rates in flow-diverter stents. 15 ) Specifically, it has been shown that a vessel angle of 20° or more likely indicates stable aneurysms, regardless of neck or aneurysm size.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 14 ) Therefore, straightening the parent artery with a stent may be the optimal way to reduce the recurrence of intracranial bifurcation aneurysms. 13 ) It has also been reported that parent artery straightening is likely to be involved in higher occlusion rates in flow-diverter stents. 15 ) Specifically, it has been shown that a vessel angle of 20° or more likely indicates stable aneurysms, regardless of neck or aneurysm size.…”
Section: Discussionmentioning
confidence: 97%
“…The hemodynamic effects of intracranial bifurcation aneurysms have been reported to be significantly improved by straightening the parent artery with flow diversion by metallic coverage. 13 ) Vascular straightening by stenting dramatically alters apex hemodynamics in a favorable direction by blunting apical pressure, including the narrowing and migration of the flow impingement zone. 14 ) Therefore, straightening the parent artery with a stent may be the optimal way to reduce the recurrence of intracranial bifurcation aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al ( 30 ) reported an outer curve aneurysm with lower vascular tortuosity was more similar to a bifurcation aneurysm and more likely to recur. Leng et al ( 31 ) and Wan et al ( 32 ) both pointed out that better hemodynamic changes can be achieved by using stents to straighten blood vessels. The risk of recurrence can be reduced by weakening the hemodynamic characteristics of bifurcation aneurysms, which was also consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative aneurysm rupture is one of the significant risk factors for early serious complications ( 17 ), and the risk of intraprocedural rupture is significantly high during coiling, especially in heteromorphic or very small aneurysms ( 31 , 32 ). Flow velocity in the aneurysm and wall shear stress are two important hemodynamic parameters associated with the growth and rupture of intracranial aneurysms ( 7 , 8 ), and could be eliminated by coiling the aneurysm more intuitively ( 33 , 34 ). In our study, two cases with acute cerebral hemorrhage were all in the SAC group, in our experience, complicated aneurysms treated with Leo-assisted coiling could not be packed too densely.…”
Section: Discussionmentioning
confidence: 99%